A study of Medical and Psychosocial Challenges in Immigrants with Poliomyelitis - Lillian Festvåg; Johan K. Stanghelle; Nils Erik Gilhus; Anne-Kristine Schanke (Fysioterapeuten, 2022)
Objective: To explore the health and psychosocial situation among non-Western immigrants to Norway with polio sequelae.